1998
DOI: 10.1021/jo971283p
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereochemistry of Gas-Phase Acid-Induced Nucleophilic Substitutions on Chiral Allylic Alcohols1

Abstract: The regio- and stereochemistry of the nucleophilic attack of (S)-trans-3-hexen-2-ol (MS ) and (S)-trans-4-hexen-3-ol (ES ) on the corresponding O-protonated (L = H) and -methylated (L = CH3) derivatives (MSL+ and ESL+ ) are investigated in the gas phase at 40 °C (720 Torr). The MSL+ and ESL+ intermediates are produced in the gas phase by the attack of the ionic Brønsted and Lewis acids, formed by stationary γ-radiolysis of bulk CH3Cl, on the corresponding chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Although the aim of this study was not to describe closely the nature of the mechanism involved in the acid‐induced intramolecular nucleophilic substitution or α–β elimination reaction, some remarks should be made. Consistent with many studies reported previously, such behavior could be induced by an elongation of the peroxide O δ+ —C bond and driven by a carbocation stabilization which will decrease the energy level of the transition state of the reaction 21–33. Prior to dissociation, this activated ion undergoes isomerization into an ion–neutral complex which evolves towards two possible a and b pathways (Scheme ) 34.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Although the aim of this study was not to describe closely the nature of the mechanism involved in the acid‐induced intramolecular nucleophilic substitution or α–β elimination reaction, some remarks should be made. Consistent with many studies reported previously, such behavior could be induced by an elongation of the peroxide O δ+ —C bond and driven by a carbocation stabilization which will decrease the energy level of the transition state of the reaction 21–33. Prior to dissociation, this activated ion undergoes isomerization into an ion–neutral complex which evolves towards two possible a and b pathways (Scheme ) 34.…”
Section: Resultssupporting
confidence: 74%
“…for a microcanonical system (for a given value of energy e ), the magnitude of the microcanonical rate constant k (e) of the reaction yielding [ II + H] + from [ II + CH 3 OH 2 ] + , appears so tenuous that the reactive species is involved in another competing processes such as intramolecular internal nucleophilic substitution and α–β elimination (Scheme ). These kinds of reactions are known to proceed via a highly organized transition state and require a very specific orientation of groups involved in the reaction 32, 33. Such a competition illustrates low values of the microcanonical rate constant for the dissociation of the complex [ II + CH 3 OH 2 ] + leading to the formation of the ionic species [ II + H] + .…”
Section: Discussionmentioning
confidence: 99%
“…The chemistry of allylic derivatives and the propensity of their nucleophilic substitution reactions to result in rearranged products have been the subject of intensive study for over a century 1–3. However, the exact structures of the possible products formed, as well as their relative distribution, are often rather unpredictable because they are dependent on the allylic substrate and on a range of reaction variables.…”
Section: Introductionmentioning
confidence: 99%
“…These differences can be exploited (i.e., by comparison to data for known standards) and used to determine the enantiomeric purity of a sample. Cooks [3][4][5][6][7][8][9][10][11][12][13][14][15][16], Dearden , Lebrilla [21][22][23][24][25][26], Speranza [27][28][29][30][31][32][33][34][35], and others have provided useful examples of this approach to stereochemical analysis.…”
mentioning
confidence: 99%
“…In general, these processes have been probed in the condensed phase, but there is no reason why mass spectrometry could not also be used to screen gas phase reactions for stereoselectivity [35,36]. An advantage of this approach is that in the solvent-free environment of the gas phase, it is possible to gain a clear understanding of the molecular interactions that lead to stereoselectivity in a chemical transformation.…”
mentioning
confidence: 99%